VARIETY OF COGNITIVE PRACTICES IN THE EDUCATIONAL SPACE OF MODERN UKRAINIAN SOCIETY - Dovhan, Anatolii; Perenchuk, Olga (Mountain School of Ukrainian Carpaty, 2022)
An attempt to analyze the manifestation of some postmodern ideas of cognitive optimism in educational practices of modern Ukrainian society has been made in the article under discussion. The focus has been made on the fact, that the gnoseological paradigm of social diffusion producing in human relations can cause the destruction of everyday life stereotypes of an ordinary citizen whose outlook was influenced by the historic traditions of national relationships. The novelty of the present state of Ukrainian society’s everyday life is that its social structure has been disorganized, and new social subjects have appeared whose heterogeneous outlooks form complex mosaics of the education routine. The everyday consciousness of an individuum pressed by real-life facts has to find a practical way out of the conflicting situations, experiencing them in their own way chosen by them. Thus, the cognitive function of his will has been promoted to introduce other variations in educational practices. Pluralism of thoughts has caused some essential changes in the possibilities of the information behavior of a person. In such a versatile and content-rich information pedagogical environment (not always socially high-quality as for values), the will freedom has been recognized as a unilateral and purposeful tool to maximize the amount of not always enough meaningful messages, monologues, and dialogues even in the teaching-educational process of higher educational establishments.